Higher Order Organization of the mtDNA: Beyond Mitochondrial Transcription Factor A - Mishmar, Dan; Levin, Rotem; Naeem, Mansur M.; Sondheimer, Neal (Frontiers in Genetics, 2019)
The higher order organization of eukaryotic and prokaryotic genomes is pivotal in the regulation of gene expression. Specifically, chromatin accessibility in eukaryotes and nucleoid accessibility in bacteria are regulated by a cohort of proteins to alter gene expression in response to diverse physiological conditions. By contrast, prior studies have suggested that the mitochondrial genome (mtDNA) is coated solely by mitochondrial transcription factor A (TFAM), whose increased cellular concentration was proposed to be the major determinant of mtDNA packaging in the mitochondrial nucleoid. Nevertheless, recent analysis of DNase-seq and ATAC-seq experiments from multiple human and mouse samples suggest gradual increase in mtDNA occupancy during the course of embryonic development to generate a conserved footprinting pattern which correlate with sites that have low TFAM occupancy in vivo (ChIP-seq) and tend to adopt G-quadruplex structures. These findings, along with recent identification of mtDNA binding by known modulators of chromatin accessibility such as MOF, suggest that mtDNA higher order organization is generated by cross talk with the nuclear regulatory system, may have a role in mtDNA regulation, and is more complex than once thought.